Análisis financiero de los hoteles de la ciudad de Manta y la incidencia del COVID-19 en el período 2019 - 2020 - Mendoza Guadamud, María Dayana (2023)
The main purpose of this research was to evaluate the financial situation of the Oro Verde, Cabañas Balandra and Los Almendros hotels in the city of Manta and the incidence of Covid-19 in the period 2019-2020. For which the bibliographic and field research was used, the descriptive, deductive, inductive and analytical methods, population and convenience sampling, as techniques the observation and interview stand out, and, as tools, the observation guide, guide of interview and Delphi method. To obtain the results, three methodological phases were structured, in the first phase a horizontal and vertical analysis was carried out to identify the variations and trends of the hotels in the period 2019-2020, then in the second phase, the indicators of solvency, management, liquidity and profitability to know the economic-financial development of the hotels, and finally in the third phase, the incidence of Covid-19 was identified through the application of the interview to the managers of the hotels and with it tabulation and analysis of the data was performed. The investigation concludes that the financial field of the Los Almendros hotel presented lower liquidity and profitability, as well as solvency and management problems, and, in the Covid-19 variable, it was shown that the hotels did not maintain their commercial continuity in the 2020 period, which generated decrease in profitability, with the exception of the Oro Verde hotel, which was not affected due to the capital and resources it had to deal with the health crisis.